Analisis Program Integrated Communication Komunitas Brigata Curva Sud (BCS) dalam Membentuk Kesadaran Suporter Sepak Bola PSS Sleman - Niatami, Silviyana Dyah; Luga, Noyanta; Rachmawati, Oky (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2020)
This study aims to determine the integrated communication program community of Brigata Curva Sud (BCS) in shaping the awareness of PSS Sleman football supporters. The research method in this research is qualitative, by conducting interviews with four speakers. The conclusion of this research is Brigata Curva Sud utilizing all human resources in the community. In every message Brigata Curva Sud uses propaganda techniques. The purpose of all the propaganda messages conveyed by Brigata Curva Sud is to foster and maintain love for PSS Sleman. Fanaticism is built in every member of Brigata Curva Sud. This fanaticism makes it easier to deliver messages to BCS members. Brigata Curva Sud not only uses propaganda techniques but also embodies other forms of Integrated Communication.